Improving the Nutrient Quality of Juice Waste Mixture by Steam Pressure for Poultry Diet - Mahata, Maria Endo; Rizal, Yose; Wu, Guoyao (Pakistan Journal of Nutrition, 2012)
The problem of juice waste mixture as poultry diet was high in crude fiber and low in metabolizable energy contents. Experiments were performed to improve the nutrient quality of juice waste mixture by using steam pressure. The first experiment was designed in a completely randomized design with 4 different incubation times of juice waste mixture (0, 15, 30, and 45 minutes) in Autoclave (15 psi pressure and 121°C), and each treatment was replicated 5 times. Measured variables were crude fiber, crude protein, crude fat. The second experiment was to compare of crude fiber, crude protein, ether extract, NDF, ADF, cellulose, hemi-cellulose, lignin, nitrogen retention, amino acid profile, and metabolizable energy of juice waste mixture between treated vs. untreated one. The results showed that the crude fiber, crude protein, and crude fat of juice waste mixture were significantly affected (P